PrivacyMod: Controlling and Monitoring Abuse of Privacy-Related Data by Android Applications - Silva, Pablo; Amorim, Vicente J. P.; Ribeiro, Filipe N.; Muzetti, Igor (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
The Android Open Source Project, currently managed by Google, provides a software stack for Android operating system. Despite the efforts to create a scalable and secure OS, Google is failing to deal with users' privacy information. Any Android application (including third-party ones) can retrieve sensible data from devices without providing any notification to the user. This paper presents a new Android OS source code extension module to monitor and control relevant privacy data on third-party applications. Once a data operation of this type is detected, the user is notified in real time, creating a live history of use/abuse. Results showed many traditional applications making abuse of users' device confidential information. Our proposed mechanism enables the user to be aware and manage the use of every sensible information on his device.